1992
DOI: 10.1159/000126124
|View full text |Cite
|
Sign up to set email alerts
|

Selective Venous Sampling in the Differential Diagnosis of ACTH-Dependent Cushing’s Syndrome

Abstract: Bilateral simultaneous inferior petrosal sinus sampling, associated with the oCRH stimulation test (100 µg i.v. as a bolus) was performed in 22 patients with Cushing’s syndrome and no signs of pituitary abnormalities. Catheters were inserted into both femoral veins. More than one site in the superior and inferior vena cava was sampled before reaching the inferior petrosal sinuses. Blood samples for ACTH and β-endorphin were gently aspirated from both petrosal sinuses and from a peripheral vein simultaneously. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Moreover, this study shows, for the first time to our knowledge, the lack of ISG for GH, PRL, TSH, FSH and LH as well as of p-endorphin in patients with EAS. These data, although obtained in only 4 cases are in agreement with the report of p-endorphin ISG in 2 other cases of EAS [24] and indicate that the multiple hormone evalua tion might improve the diagnostic accuracy of IPSS. Finally, the question of whether IPSS can be confirmed in clinical practice as a reliable tool to localize the site of the pituitary microadenoma in CD is still unresolved.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, this study shows, for the first time to our knowledge, the lack of ISG for GH, PRL, TSH, FSH and LH as well as of p-endorphin in patients with EAS. These data, although obtained in only 4 cases are in agreement with the report of p-endorphin ISG in 2 other cases of EAS [24] and indicate that the multiple hormone evalua tion might improve the diagnostic accuracy of IPSS. Finally, the question of whether IPSS can be confirmed in clinical practice as a reliable tool to localize the site of the pituitary microadenoma in CD is still unresolved.…”
Section: Discussionsupporting
confidence: 89%
“…Al though it has been suggested that corticotroph microade nomas preferentially arise in the central mucoid core of the anterior lobe [25,26], these tumors can arise any where in the sella including the intermediate lobe [20][21][22]27]. In our series the correct localization of the side of the adenoma was obtained in 87% of cases and in only a minority of patients was the adenoma falsely localized (21 %): the percentage of cases was, however, comparable to the findings of other authors [4,5,24], Furthermore, no patient with poststimulation gradient reversal was found [28].…”
Section: Discussionsupporting
confidence: 89%
“…Morphological assessment was performed by pituitary and adrenal computerized tomography and/or magnetic resonance imaging, and adrenal scintiscan with 6-methyl-75Se-seleniomethyl-19-norcholesterol. When indicated, bilateral petrosal sinus sampling was also employed (Boscaro et al, 1992). All patients were interviewed while on remission after surgery, pituitary irradiation or pharmacological treatment with inhibitors of steroid production (Sonino et al, 1988(Sonino et al, , 1991, and therefore not in the hypercortisolaemic state.…”
Section: Patientsmentioning
confidence: 99%
“…Morpho logical assessment was performed by pituitary and adrenal computer ized tomography (CT) and/or magnetic resonance imaging (MRI), and adrenal scintiscan with 6-methyl-75-scleniomcthyl-19-norcholesterol. When indicated, bilateral petrosal sinus sampling was also employed [18][19][20][21]. Patients of both groups all showed good cortisol suppression with high-dose dexamethasone test (table 1).…”
Section: Methodsmentioning
confidence: 99%